2021
DOI: 10.5603/ep.a2021.0010
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of microRNAs as the risk factor of lymph node metastasis in papillary thyroid carcinoma: systematic review

Abstract: Papillary thyroid carcinoma (PTC) has an excellent prognosis with a relatively low mortality rate, but a small portion of PTC patients suffer from an aggressive form of the disease. In such cases early detection of lymph node metastasis (LNM) is as paramount as it is problematic.The routine use of central neck lymph node dissection is not recommended. New methods to detect LNM are needed. MicroRNAs are a potential biomarker for diagnosis and prognosis of PTC. In this review we summarise the current knowledge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…Of these, the three most divergent miRNAs, miR4324, miR200B, miR125A, were selected for further validation. After the literature review, two more miRNAs, miR146B, miR221, which have been mainly described for differentiating both PTC with benign thyroid disease and more aggressive forms of PTC, were selected for further testing [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, the three most divergent miRNAs, miR4324, miR200B, miR125A, were selected for further validation. After the literature review, two more miRNAs, miR146B, miR221, which have been mainly described for differentiating both PTC with benign thyroid disease and more aggressive forms of PTC, were selected for further testing [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the last decade, several studies have been conducted to identify miRNAs associated with PTC metastasis [ 20 ]. Chou and co-authors demonstrated that miR146B expression is an independent risk factor for poor prognosis in PTC [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic PTC were excluded to obtain homogenous PTC cohort, which was also helpful to comprehensively describe tumor-initiating alterations in miRNA expression pattern [ 37 ]. Literature data suggest distinct miRNA expression pattern associated with lymph node metastasis in PTC patients [ 38 ]. It is worth noting that the data on the diagnostic value of the miRNA profile in differentiation between metastatic PTC and non-metastatic PTC patients are limited.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA dysregulation has been identified as a hallmark of human malignancies (10,29) and may be correlated with clinicopathological characteristics and disease activity of cancer (30)(31)(32). Several studies have demonstrated that miRNAs play an important role in the metastasis and progression of thyroid cancer (33)(34)(35)(36)(37)(38)(39). In the present study, we showed for the first time that miR-29b-3p expression was downregulated in PTC tissues as compared to normal tissues and was significantly negatively correlated in terms of tumor size, local lymph node metastasis, and TNM stage in patients with PTC.…”
Section: Discussionmentioning
confidence: 99%